Pembuatan Komik Strip Cerita Rakyat Si Raja Tambun Sibisa - Susanti Sarah Dina Tambunan (Jurnal Dirosah Islamiyah, 2024)
The Folktale of Si Raja Tambun is a folktale originating from Sibisa Village, Ajibata District, Toba Samosir Regency. As part of this research, a German language comic about folklore was developed on Canva media. The development theory used is Richey and Klein's development theory which is divided into three stages, namely: planning, creation and evaluation. The primary data sources in this research are interviews and observations conducted with residents and traditional leaders in Sibisa Village, Tobasa. And the secondary data sources used are archives and documents related to the history of Si Raja Tambun. This research is development research using qualitative descriptive research methods. The result of this research is that the product developed through Canva in the form of comics has been assessed by media validators and has a very good rating and is suitable as learning material.